ULTRASONOGRAPHIC EVALUATION OF UTERINE INVOLUTION IN PGF2α TREATED COWS - ALAGAR, S; SELVARAJU, M; NAPOLEAN, RE; DORAISAMY, KA (The Indian Journal of Animal Reproduction, 2016)
Eighteen postpartum Holstein Friesian crossbred cows (lactation, 2 - 5) were randomly and equally divided to receive (i.m.) on day 2 postpartum either 25 mg PGF2α (Dinoprost Tromethamine) or 5 ml normal saline. In PGF2α group, cervical and uterine involution, as detected per rectally, progressed rapidly compared to controls. Ultrasonography of cervix and uterine body on day 2, 10, 20 and 30 postpartum, revealed that cervical and uterine diameter decreased quickly in PGF2α group. In brief, exogenous PGF2α administration on day 2 postpartum lead to better cervical and uterine involution by day 30 postpartum in crossbred cows.
Keywords: Cervix; Involution; PGF2α; Postpartum; Uterus